1992
DOI: 10.1002/ange.19921040629
|View full text |Cite
|
Sign up to set email alerts
|

Ein neuer Reaktionstyp bei der Umsetzung von Enaminen mit 1,4‐Diphenyl‐2‐buten‐1,4‐dion zu Käfigverbindungen

Abstract: Dimethylphenol durch Veresterung und intramolekulare Arylkupplung synthetisieren l a~s e n [~~. Die Ergebnisse der Ringoffnungsexperimente sind in Tabelle 1 zusammengefaat.Die Leistungsfahigkeit des Verfahrens zeigt sich in den schon mit den monocyclischen Derivaten 3a-c erzielten guten Ergebnissen, vor allem aber in den zum Teil exzellenten Atropisomerenverhaltnissen mit den bicyclischen Reagentien 4a-c, die bei praktisch quantitativem Umsatz durchweg bei mindestens 90: 10 liegen. Dabei wurden die mit Abstand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Thus, it was shown that the interaction of cyclic enamines 21 a – d with dibenzoylacetylene 22 leads to the formation of bicyclic cyclobutene derivatives 23 a – d , which, except for 23 a , instantly isomerize to monocyclic 1,3‐dienes 24 b – d (Scheme 7). [11] For further convenience of presenting the material, we depicted frequently used enamines in this review in Figure 2.…”
Section: Carbocyclization Reactionsmentioning
confidence: 99%
“…Thus, it was shown that the interaction of cyclic enamines 21 a – d with dibenzoylacetylene 22 leads to the formation of bicyclic cyclobutene derivatives 23 a – d , which, except for 23 a , instantly isomerize to monocyclic 1,3‐dienes 24 b – d (Scheme 7). [11] For further convenience of presenting the material, we depicted frequently used enamines in this review in Figure 2.…”
Section: Carbocyclization Reactionsmentioning
confidence: 99%